Inside Microsoft Dynamics AX 2012 R3 (Microsoft Press, 2014)
Fully updated for Microsoft Dynamics AX 2012 R3! Dig into the architecture and internals of Microsoft Dynamics AX 2012 R3 - with firsthand insights from the team that designed and developed it. Deepen your knowledge of the underlying frameworks, components, and tools - and deliver custom ERP applications with the extensibility and performance your business needs. Useful for Microsoft Dynamics AX solution developers at all levels, this guide will provide max benefit to those who understand OOP, relational database, and Transact-SQL concepts. Gain best practices, patterns, and techniques to: Exploit interoperability with Microsoft Visual Studio tools Work with MorphX and avoid common pitfalls with X++ code Use Enterprise Portal with ASP.NET and SharePoint for rich web-based apps Simplify process automation with built-in workflow infrastructure See how the runtime implements security and configuration Design and customize the user experience Gain greater control over complex batch jobs Customize the prebuilt BI solution and reporting Test applications, publish services, and optimize performance.